Pembuatan Tepung Bengkuang sebagai Bahan Baku Makanan - Purwanti Retno Sari; Tamrin Tamrin; Winda Rahmawati; R. A. Bustomi Rosadi (Jurnal Agricultural Biosystem Engineering, 2022)
Processing of bengkuangin other products is flour which has many uses. Fresh bengkuang contains 2.1 g - 10.7 g starch and 1 g - 2.2 g protein. The purpose of this study is to eliminate the moisture content of the material by drying and turning it into flour as a raw material for food mixtures, so that its shelf life is longer. This research will have been carried out in March 2019 until July 2019 in the Bioprocessing and Post Harvest Laboratory, Water and Land Resources Laboratory, Department of Agricultural Engineering, Faculty of Agriculture, University of Lampung, Bandar Lampung, Laboratory of Agricultural Product Processing, Pati Laboratory and Carbohydrates, Department of Agricultural Product Technology, Faculty of Agriculture, University of Lampung. This research method with the experimental method. Temperature treatment and material thickness. The analysis carried out was a test of vitamin C, moisture content, aroma, color. The results of this study are the analysis of vitamin C, the higher the temperature, the vitamin C content will be damaged or lost due to evaporation. The water content of bengkuang slices has decreased, namely at 0 minutes 85% water content and after undergoing the process of pengovenan to 10%. The aroma of bengkuang flour is preferred by panelists at 50 ° C and 70 ° C, while at 90 ° C the panelists are less favored. The colors carried out by the statistical test had no effect between temperature on color and thickness had no effect on color.